The Evolution and Implications of CSR in Indonesian Tobacco Companies: A Bibliometric Analysis Based on Business Law Theory - Suparnyo, Suparnyo; Zamroni, Edris; Kartiko, Ari; Kasheem, Majdy (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2024)
Corporate Social Responsibility (CSR) is part of a company's responsibility in ensuring the welfare of the surrounding community. Even so, CSR from the cigarette industry contains many dilemmas both from the social, health and legal aspects that cover it. This research aims to determine research trends regarding the CSR paradigm from the cigarette industry as well as the business law perspective that is the legal basis. The method used is bibliometric analysis using the R Studio and Biblioshiny applications. The main database used is scopus.com from the year 1992-2024. The results found 36 publications that studied the CSR theme of the cigarette industry. The main focus of the study is still within the scope of the dynamics of the tobacco industry and the human and health side of the industry. There are only 9 articles that discuss CSR in the cigarette industry and 7 articles that discuss the legal ethics of implementing CSR in the cigarette industry. Not only has a study been conducted on the business legal side of CSR in the cigarette industry. This is a huge opportunity for future researchers to conduct a more comprehensive study in order to get a complete view of the legal aspects in implementing CSR in the cigarette industry both in Indonesia and in the world.